AGROLANDSCAPES OF THE MIDDLE POBUZHZHYA: MODERN CONDITIONS AND PROBLEMS OF THE USE - Кульбіда, Л. С. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The wide-ranging extensive land use, excessive plowing of territories without their taking into account the landscape features, the saturation of crop rotation by cultivated crops, lack of organic manure and other adverse factors have led to the development of soil erosion and degradation of agricultural landscapes. The landscapes of the Middle Pobuzhzhya are the most eroded in Vinnytsya region because the northern region’s soils are the most generous. But now they have 6 - 8% less organic matter than their natural analogues. One of the first anthropogenic pressures was experienced by the floodplains. The fertile floodplain provides a rich harvest, therefore they are ploughed and heavily used. The prolonged economic development and natural floodplain of natural resources has led to the complete replacement of natural landscapes by man-made. According to the scientists, it is the transfer of arable land in layers that ensure their protection and preservation for future generations. The perennial grasses protect the soil from erosion better. The organization of agriculture on the basis of landscape involves the study and consideration of natural and anthropogenic resources of a certain territory and its differentiation by lands soil - landscape, hydro- logical and other conditions. Practical implementation of environmentally sustainable land use will only be possible after the creation of an appropriate legislative framework. There are some requirements for immediate adoption in the new edition of the law on payment for land, money and their growth of class assessment, the withdrawal of dangerous erosion of arable land and degraded lands, protection of soil and the corresponding state program that will determine the sources of financing of these measures.